The Day After Tomorrow : A Handbook on the Future of Economic Policy in the Developing World - Canuto, Otaviano; Giugale, Marcelo (World Bank, 2012)
Development economists are paid to look into the future. They ask not only how things work today, but also how a new policy, program, or project will make them work tomorrow. They view the world and history as a learning process, past and present are just inputs into thinking about what's coming. It is that appetite for a vision of the future that led us to invite some 40 development economists, most of them from the World Bank's poverty reduction and economic management network, an epicenter of the profession, to tell us what they see on the horizon of their technical disciplines and of their geographic areas of specialization. The timing could not be better. The 2008-09 global financial crises shook the ground under the conventional wisdom that had been held as true for decades. From what the role of governments should be in markets to which countries will be the engines of the world's economy, from what people need to leave poverty to what businesses need to stay competitive, it is all up for reexamination. This synthesis provides an account of what the author heard. It is not meant to be comprehensive. Instead, it picks from each chapter what is new, what is likely to change, and what will be different in the future.